Task‐based functional magnetic resonance imaging prediction of postsurgical cognitive outcomes in temporal lobe epilepsy: A systematic review, meta‐analysis, and new data. Issue 2 (29th December 2022) - Crow, Andrew J. D.; Thomas, Alisha; Rao, Yash; Beloor‐Suresh, Ashithkumar; Weinstein, David; Hinds, Walter A.; Tracy, Joseph I.
Abstract: Task‐based functional magnetic resonance imaging (tfMRI) has developed as a common alternative in epilepsy surgery to the intracarotid amobarbital procedure, also known as the Wada procedure. Prior studies have implicated tfMRI as a comparable predictor of postsurgical cognitive outcomes. However, the predictive validity of tfMRI has not been established. This preregistered systematic review and meta‐analysis (CRD42020183563) synthesizes the literature predicting postsurgical cognitive outcomes in temporal lobe epilepsy (TLE) using tfMRI. The PubMed and PsycINFO literature databases were queried for English‐language articles published between January 1, 2009 and December 31, 2020 associating tfMRI laterality indices or symmetry of task activation with outcomes in TLE. Their references were reviewed for additional relevant literature, and unpublished data from our center were incorporated. Nineteen studies were included in the meta‐analysis. tfMRI studies predicted postsurgical cognitive outcomes in left TLE ( ρ ̂ = −.27, 95% confidence interval [CI] = −.32 to −.23) but not right TLE ( ρ ̂ = −.02, 95% CI = −.08 to .03). Among studies of left TLE, language tfMRI studies were more robustly predictive of postsurgical cognitive outcomes ( ρ ̂ = −.27, 95% CI = −.33 to −.20) than memory tfMRI studies ( ρ ̂ = −.27, 95% CI = −.43 to −.11). Further moderation by cognitive outcome domain indicated language tfMRI predicted confrontation naming ( ρ ̂ = −.32, 95% CI = −.41 to −.22) and verbal memory ( ρ ̂ = −.26, 95% CI = −.35 to −.17) outcomes, whereas memory tfMRI forecasted only verbal memory outcomes ( ρ ̂ = −.37, 95% CI = −.57 to −.18). Surgery type, birth sex, level of education, age at onset, disease duration, and hemispheric language dominance moderated study outcomes. Sensitivity analyses suggested the interval of postsurgical follow‐up, and reporting and methodological practices influenced study outcomes as well. These findings intimate tfMRI is a modest predictor of outcomes in left TLE that should be considered in the context of a larger surgical workup.